Stationary distributions for retarded stochastic differential equations without dissipativity - Chenggui Yuan (Stochastics, 2017)
In this paper, we use variation of constants formula to investigate the stationary distribution for stochastic differential delay equations. Under certain conditions (without dissipative conditions) we prove the existence and uniqueness for stochastic differential delay equations.